Manajemen Tenaga Kependidikan di Sekolah Dasar Islam Terpadu - Hanifah Noviandari; Kharis Syuhud Mujahada (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to look at the management of teachers and educational staff in one of the primary schools. The effectiveness of the learning process and the achievement of students is largely dependent on the performance of the education personnel, which includes instructors and other staff members. Teachers, staff, and principals served as the data sources for this qualitative descriptive study. Interviews, observations, and document studies are the methods utilized for gathering data. Triangulation of methods and sources is used to verify the accuracy of the data. The Miles, Huberman, and Saldana interactive analysis approach, which consists of three stages—data condensation, data presentation, and conclusion/verification—is used for data analysis. The findings indicated that the administration of educational people in schools involves six stages, including planning, recruitment, job placement, remuneration, and evaluation.  Steps in the recruitment process include receiving cover letters, conducting selection interviews, checking references and applicants' backgrounds, evaluating applicants' health, and interviewing school principals. Through discussions, the division and placement of work is done in accordance with academic credentials and talents. Staff members in the education sector are paid in the form of a salary or an honor based on their performance. Working groups for teachers (KKG) and school principals (KKKS) are used to create competencies, along with ongoing professional development. (PKB). The principal and supervisors conduct evaluations on a regular basis. Administrative monitoring is also conducted, as well as a semesterly evaluation of teacher performance.